If it's not what You are looking for type in the equation solver your own equation and let us solve it.
38+15k=8k+32
We move all terms to the left:
38+15k-(8k+32)=0
We get rid of parentheses
15k-8k-32+38=0
We add all the numbers together, and all the variables
7k+6=0
We move all terms containing k to the left, all other terms to the right
7k=-6
k=-6/7
k=-6/7
| -13.5=2.7k | | b-8/13=-9 | | 28x-4=4(7x-1) | | -5(6-5x=2(7x-4) | | 59 =10k−12 | | 2(x2)=1 | | -4=p/11 | | 2(x)=2×3(x−1) | | 5x+24)=9x-17 | | 17=8x+1 | | x/26=6 | | 7(2x-1)-8=-3(x+5) | | 6(n−10)=5n−42−2n | | (3/2)x=12 | | 11(n+4)–19= | | x/26=67 | | (2x-9)+(x+7)=115 | | -8=12+4d | | -2(n+1)+3=n-3n+1 | | 10h+h=34 | | 9=-3p-4+4p | | -k=-(-8k) | | 3/2m+2=1/6m-3 | | -32r+5=3r | | –8k−9=–7k | | 8-1x=3x-4 | | 2x+6x-1=120 | | -1/24x+2=19 | | 3x-20+x=100 | | 13+4(y+5)=-3 | | −12=8+4x | | 2(y-6)+4=16 |